Frequency of cancer events with saxagliptin in the SAVOR‐TIMI 53 trial. Issue 2 (27th November 2015) - Leiter, L. A.; Teoh, H.; Mosenzon, O.; Cahn, A.; Hirshberg, B.; Stahre, C. A. M.; Hoekstra, J. B. L.; Alvarsson, M.; Im, K.; Scirica, B. M.; Bhatt, D. L.; Raz, I.; et al.
Abstract : The Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus (SAVOR)–Thrombolysis in Myocardial Infarction (TIMI) 53 trial randomized trial of 16 492 patients (placebo, n = 8212; saxagliptin, n = 8280) treated and followed for a median of 2.1 years afforded an opportunity to explore whether there was any association with cancer reported as a serious adverse event. At least one cancer event was reported by 688 patients (4.1%): 362 (4.3%) and 326 (3.8%) in the placebo and saxagliptin arms, respectively (p = 0.13). There were 59 (0.6%) deaths adjudicated as malignancy deaths with placebo and 53 (0.6%) with saxagliptin. Stratification by gender, age, race and ethnicity, diabetes duration, baseline glycated haemoglobin and pharmacotherapy did not show any clinically meaningful differences between the two study arms. The overall number of cancer events and malignancy‐associated mortality rates were generally balanced between the placebo and saxagliptin groups, suggesting a null relationship with saxagliptin use over the median follow‐up of 2.1 years. Multivariable modelling showed that male gender, dyslipidaemia and current smoking were independent predictors of cancer. These randomized data with adequate numbers of cancer cases are reassuring but limited, by the short follow‐up in a trial not designed to test this hypothesis.